Pengaruh Media Busy Book Terhadap Kemampuan Literasi Anak Usia Dini - Rafly, Nur Aliah; Herman, Herman; Amal, Azizah; Rusliana, Faradillah (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to determine the effect of busy book media on the literacy skills of children aged 5-6 years at Teratai Makkasar University Kindergarten. The research approach used is a quantitative approach with a Quasi Experimental Design research type using a Non-equivalent Control Group design. The population in this study was 55 children. Sampling used Purposive Sampling technique. The sample consisted of 32 children, 16 children in the experimental group who used busy book media and 16 children in the control group who used alphabet poster media. The data analysis technique used was descriptive statistical analysis and parametric statistical analysis using normality tests, homogeneity tests and hypothesis tests using SPSS version 21. The results showed a significant increase in children's literacy skills in the experimental group with an average value of 23.75, while the control group had an average value of 17.44. Data analysis obtained from the test conducted was Asym (2-tailed) = 0.000 <0.05 meaning  was accepted and  was rejected. Thus, the literacy skills of children in the experimental group were better than those of the control group, this proves that the use of busy book media has a significant influence on the literacy skills of children aged 5-6 years at Makassar University Teratai Kindergarten